Efficacy of Telerehabilitation Protocols for Improving Functionality in Post-COVID-19 Patients - Jose Luis Estela-Zape; Valeria Sanclemente-Cardoza; Leidy Tatiana Ordoñez-Mora (Life)
Background and Aims: Telerehabilitation is essential for the recovery of post-COVID-19 patients, improving exercise tolerance, dyspnea, functional capacity, and daily activity performance. This study aimed to describe telerehabilitation protocols specifically designed for individuals with post-COVID-19 sequelae. Materials and Methods: A systematic review was conducted with registration number CRD42023423678, based on searches developed in the following databases: ScienceDirect, Scopus, Dimensions.ai and PubMed, using keywords such as “telerehabilitation” and “COVID-19”. The final search date was July 2024. The selection of studies involved an initial calibration process, followed by independent filtering by the researchers. The selection criteria were applied prior to critical appraisal, data extraction, and the risk of bias assessment. Results: After reviewing 405 full-text papers, 14 articles were included that focused on telerehabilitation interventions for post-COVID-19 patients. These interventions were designed for remote delivery and included exercise protocols, vital sign monitoring, and virtual supervision by physical therapists. The studies reported improvements in physical function, muscle performance, lung capacity, and psychological outcomes. Significant gains were observed in strength, mobility, and functional capacity, as well as reductions in dyspnea, fatigue, and improvements in quality of life, particularly in social domains. Intervention protocols included aerobic, strength, and respiratory exercises, monitored using tools such as heart rate monitors and smartphones. Conclusions: Telerehabilitation positively impacts lung volumes, pulmonary capacities, dyspnea reduction, functionality, muscle performance, and independence in post-COVID-19 patients.